Problematika Pembelajaran Pendidikan Agama Islam Kurikulum 2013 di SMPN 2 Wonosalam Jombang - Eko Hadi Wardoyo; Anis Novita Sari (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2018)
This study aims to determine the Problem of Islamic Education K-13 Learning at SMPN 2 Wonosalam Jombang, as well as to find out the school strategy of SMPN 2 Wonosalam Jombang in overcoming the problems of K-13 PAI learning so that it can run effectively. This study uses a qualitative descriptive approach, with methods of collecting observation data, interviews and documentaries, then data reduction, namely classification and concentration of data already obtained in the field; the presentation of data is collecting data in a structured manner by giving the possibility of a conclusion. While the data analysis uses deductive and inductive analysis. The results showed that: The problem of learning K-13 Islamic religious education at SMPN 2 Wonosalam Jombang was not too prominent due to the application of appropriate learning methods, and supported by competent human resources. The success of PAI learning can be effective if there is a synergy between all lines, both teachers, students and the local community.